2016
DOI: 10.1016/j.poly.2015.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular assembly and transfer hydrogenation catalysis with ruthenium(II) complexes of 2,6-di(1H-pyrazol-3-yl)pyridine derivatives

Abstract: )]) were screened for activity towards transfer hydrogenation of acetophenone in refluxing 2-propanol. The chloride salt catalysts are active but show a significant induction period, which may imply decomposition of the complexes during the reaction. However the activity of the PF 6 salt is much higher, which shows that competition between chloride and substrate for the metal center is a significant factor in catalysis by these compounds.4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Pincer-type ruthenium complexes bearing the protic NNN-LH 2 and its derivative are known to catalyze transfer hydrogenation of ketones with 2-propanol . To assess the impact of the central aryl group in the NCN-LH 2 pincer ligand on the catalysis, we compared the catalytic performance of the NCN pincer-type complexes 2 and the NNN analogue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pincer-type ruthenium complexes bearing the protic NNN-LH 2 and its derivative are known to catalyze transfer hydrogenation of ketones with 2-propanol . To assess the impact of the central aryl group in the NCN-LH 2 pincer ligand on the catalysis, we compared the catalytic performance of the NCN pincer-type complexes 2 and the NNN analogue.…”
Section: Resultsmentioning
confidence: 99%
“…The tunable nature of the steric and electronic parameters for these purposes is one of the distinctive traits of the pincer-type ligands. Protic pyrazole is an attractive pendant group in the pincer-type ligand to modulate the coordination sphere through hydrogen bonding and proton transfer. , During our extensive study on metal–ligand cooperation in the coordination chemistry of the protic N-heterocycles, , we have recently been interested in the NNN pincer-type 2,6-bis­(pyrazol-3-yl)­pyridine (NNN-LH 2 ; Chart ) complexes furnished with two protic pyrazole arms and investigated their proton-donating ability and metal–ligand cooperation. Particularly remarkable is the disproportionation of hydrazine into dinitrogen and ammonia catalyzed by a protic pincer-type iron complex, wherein electron transfer between the complex and the substrate molecule is associated with the proton transfer .…”
Section: Introductionmentioning
confidence: 99%
“…We and others have already demonstrated that the treatment of [RuCl 2 (PPh 3 ) 3 ] with LH 2 ‐type ligands yields the corresponding NNN pincer‐type bis(pyrazole) ruthenium(II) complexes [RuCl(LH 2 )(PPh 3 ) 2 ]Cl. In contrast, the reaction with CF 3 ‐LH 2 proved to give a complicated mixture containing a small amount of the deprotonated complex [RuCl(CF 3 ‐LH)(PPh 3 ) 2 ] ( 1 a ).…”
Section: Resultsmentioning
confidence: 99%
“…[48][49][50][51][52][53][54] Ru complexes of 3-bpp ligand derivatives have demonstrated high catalytic efficiencies for ketone-to-alcohol transfer hydrogenation, a key step in the hydrogenation of LA to GVL. [55][56][57] A heterogeneous Ru molecular catalyst with 3-bpp-based POPs, combining the function of the Ru 3-bpp catalyst system with the advantage of a solid support, would be of interest for both scientific and industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic and steric properties of 3‐bpp ligands are tunable, and multiple transition metal‐based 3‐bpp complexes have been reported for diverse catalytic applications [48–54] . Ru complexes of 3‐bpp ligand derivatives have demonstrated high catalytic efficiencies for ketone‐to‐alcohol transfer hydrogenation, a key step in the hydrogenation of LA to GVL [55–57] . A heterogeneous Ru molecular catalyst with 3‐bpp‐based POPs, combining the function of the Ru 3‐bpp catalyst system with the advantage of a solid support, would be of interest for both scientific and industrial applications.…”
Section: Introductionmentioning
confidence: 99%